To have sex or not to have sex? An online focus group study of sexual decision making among sexually experienced and inexperienced gay and bisexual adolescent men - DuBois, L. Zachary (Arch Sex Behav, 2015)
Adolescent gay and bisexual men (AGBM) are at disproportionately high risk for HIV and other sexually transmitted infections, yet healthy sexuality and HIV prevention programs grounded in experiences unique to AGBM (e.g., coming out) are lacking, as is the formative work necessary to inform such programs. A richer understanding of factors informing AGBM’s decisions to have or not have sex is needed. To fill this gap in the literature, we conducted qualitative and mixed methods analyses of data collected in online focus groups with 75 ethnically-diverse 14–18 year old AGBM across the United States. Findings suggest that many reasons why AGBM choose to have or abstain from sex mirror those noted in previous literature as influential for heterosexual adolescents (e.g., temptation, “horniness”). AGBM conveyed additional experiences/concerns that appeared unique to their sexual identity, particularly fears about pain during anal sex, and difficulties safely and accurately identifying same-sex partners. Both groups voiced reasons to wait or stop having sex. Sexually inexperienced youth said their motivations centered on wanting to avoid STIs and HIV, a desire to wait for the right partner, and the specialness of sex. On the other hand, sexually experienced AGBM said they stopped having sex if there was not an available partner they had interest in, or to improve their romantic relationship. Thus, while our findings suggest that there may be common factors across sexual identity that impact youth’s sexual decision making, healthy sexuality programs for AGBM also need to address issues specific to being gay and bisexual.